2021
DOI: 10.1136/bcr-2021-243522
|View full text |Cite
|
Sign up to set email alerts
|

Open-source automated insulin delivery systems for the management of type 1 diabetes during pregnancy

Abstract: A 40-year-old woman used an open-source automated insulin delivery system to manage her type 1 diabetes (T1D) prior to conception. The code for building the iPhone application called ‘Loop’ that carried the software for the hybrid closed-loop controller was available online. Her glycated hemoglobin before conception was 6.4%. Between 6 and 12 weeks gestation, she spent 66% time-in-range (TIR), 28% time-above-range (TAR) and 6% time-below-range (TBR). Between 18 and 24 weeks gestation, she spent 68% TIR, 27% TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Pregnancy use of DIY AID is reported in 10 individuals with; Loop (n = 7), AndroidAPS (n = 2) and OpenAPS (n = 1) [ 24 , 27 , 29 31 ]. TIR according to pregnancy targets (3.5–7.8mmol or 63-140mg/dL) was > 70% in every trimester in seven of these nine individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy use of DIY AID is reported in 10 individuals with; Loop (n = 7), AndroidAPS (n = 2) and OpenAPS (n = 1) [ 24 , 27 , 29 31 ]. TIR according to pregnancy targets (3.5–7.8mmol or 63-140mg/dL) was > 70% in every trimester in seven of these nine individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the case report studies are shown in Table 1 [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Diy Aid Case Reportsmentioning
confidence: 99%
“…Until now, most studies on APS use in pregnant women with T1DM have been case reports, [12][13][14][15][16][17][18][19][20][21][22][23][24] with only a few available randomized controlled trials (RCTs) [25][26][27][28] and non-RCTs that have small sample sizes. 29,30 We conducted the present meta-analysis of the few RCTs to assess the efficacy of APS use among pregnant women with T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing and rapid pace of development of diabetes technologies resulting in new technology such as automated insulin delivery (AID) systems, which many providers may be unfamiliar with, further exacerbates these situations where providers may be prone to remove technology that they are less experienced and familiar with. However, early research into both open source and commercial AID shows successful use of AID and diabetes self-management with technology in scenarios such as pregnancy and delivery, [5][6][7][8] surgery, 9,10 and other outpatient procedures.…”
mentioning
confidence: 99%